Helopeltis theivora dynamics and damage on cocoa clones under agronomic management in West Sumatra, Indonesia - MUNZIR BUSNIAH; SISKA EFENDI; TRIZELIA TRIZELIA; SUCI HERMANDA (Society for Indonesian Biodiversity, 2025)
Abstract. Busniah M, Efendi S, Trizelia, Hermanda S. 2025. Helopeltis theivora dynamics and damage on cocoa clones under agronomic management in West Sumatra, Indonesia. Biodiversitas 26: 5118-5124. This study analyzed the comparative resistance of cocoa clones to Helopeltis theivora in two types of cocoa plantations in West Sumatra, Indonesia. The comparison was made between plantations intensively managed by CV Scorpio and small plantations, focusing on two main clones, ICS 60 and TSH 858. The results showed that cocoa cultivation practices in intensive and smallholder cocoa plantations affected the abundance, percentage, and intensity of damage caused by H. theivora. The population and damage levels of H. theivora were higher in smallholder cocoa plantations than in intensive plantations. The type of clone cultivated also affects the abundance and damage level of H. theivora on cocoa plants. ICS 60 clone showed resistance to H. theivora compared to TSH 858 clone. Only the resistance of these clones to H. theivora was affected by cocoa cultivation practices. The resistance of these clones decreased in cocoa plantations that were not intensively managed. Secondary branches were the location of the highest damage intensity, and H. theivora showed a preference for attacking pods measuring 7-15 cm on ICS 60 and >15 cm on TSH 858. This study clearly shows that intensive cultivation practices play an important role in controlling the population of the pest H. theivora. The choice of cocoa clones is also a determining factor. The ICS 60 clone is more resistant to H. theivora. However, genetic resistance in cocoa clones is not absolute. Synergy between the selection of appropriate clones and good cultivation practices is the key to successful control of H. theivora.